Phage Biocontrol Improves Food Safety by Significantly Reducing the Level and Prevalence of Escherichia coli O157:H7 in Various Foods - Vikram, Amit; Tokman, Jeffrey I.; Woolston, Joelle; Sulakvelidze, Alexander (Journal of food protection, 2020)
Management of Shiga toxin-producing Escherichia coli (STEC), including E. coli O157:H7, in food products is a major challenge for the food industry. Several interventions, such as irradiation, chemical disinfection, and pasteurization, have had variable success controlling STEC contamination. However, these interventions also indiscriminately kill beneficial bacteria in foods, may impact organoleptic properties of foods, and are not always environmentally friendly. Biocontrol using bacteriophage-based products to reduce or eliminate specific foodborne pathogens in food products has been gaining attention due to the specificity, safety, and environmentally friendly properties of lytic bacteriophages. We developed EcoShield PX, a cocktail of lytic bacteriophages, that specifically targets STEC. This study was conducted to examine the efficacy of this bacteriophage cocktail for reducing the levels of E. coli O157:H7 in eight food products: beef chuck roast, ground beef, chicken breast, cooked chicken, salmon, cheese, cantaloupe, and romaine lettuce. The food products were challenged with E. coli O157:H7 at ca. 3.0 log CFU/g and treated with the bacteriophage preparation at ca. 1 × 106, 5 × 106, or 1 × 107 PFU/g. Application of 5 × 106 and 1 × 107 PFU/g resulted in significant reductions (P < 0.05) in E. coli O157:H7 levels of up to 97% in all foods. When bacteriophages (ca. 1 × 106 PFU/g) were used to treat lower levels of E. coli O157:H7 (ca. 1 to 10 CFU/10 g) on beef chuck roast samples, mimicking the levels of STEC found under real-life conditions in food processing plants, the prevalence of STEC in the samples was significantly reduced (P < 0.05) by ≥80%. Our results suggest that this STEC-targeting bacteriophage preparation can result in significant reduction of both the levels and prevalence of STEC in various foods and, therefore, may help improve the safety and reduce the risk of recalls of foods at high risk for STEC contamination.